(untitled) (Heritage, 2025)
The establishment of the Legation of the Kingdom of Serbia in Petrograd (1879) marked the beginning of a new chapter in Serbian-Russian relations. Diplomatic cooperation between official Belgrade and Imperial Russia was particularly extensive during the period when diplomat Miroslav Spalajković was stationed at the Serbian Legation in Petrograd. From 1900 to 1904, Spalajković served as Secretary of the Legation, and from 1913 to 1919 he held the position of Serbian Minister in the Russian capital. A notable intensification of Serbian-Russian diplomatic and political relations and contacts followed the Austro-Hungarian ultimatum to Serbia in 1914, as well as during the military operations of 1914 and 1915, and the period of temporary wartime lull in the Balkans. At that time, within the context of territorial concessions, efforts were made to satisfy the interests of certain European states in order to realize the broader war plans of the Great Powers, and to promote a final resolution of the Slavic question. From the beginning of the war until his departure from Russia, Miroslav Spalajković actively worked towards achieving Serbia’s war aims and deepening Serbian-Russian relations. This paper analyzes selected diplomatic dispatches and reports by Spalajković, which provide insight into the turbulent events during the early years of the Great War, with particular emphasis on Serbia’s position and Russia’s role in these complex wartime and geopolitical processes.